2015
DOI: 10.1074/jbc.m114.629063
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and Insulin-like Growth Factor 1 (IGF-1) Modulate Cytoplasmic Glucose and Glycogen Levels but Not Glucose Transport across the Membrane in Astrocytes

Abstract: Background: Astrocytes contain glycogen, an energy buffer in the brain. Results: Stimulation with insulin and IGF-1 decreases cytosolic glucose concentration in astrocytes without affecting glucose entry across the astrocyte plasma membrane. Conclusion: Insulin and IGF-1 boost the process of glycogen formation. Significance: This is the first high temporal resolution measurement of the decrease of glucose levels in astrocytes resulting from insulin and IGF-1 stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 83 publications
3
39
1
Order By: Relevance
“…Previous 13 C‐MRS studies in rats under light α‐chloralose anesthesia, have estimated similar (Choi, Tkác, Ugurbil, & Gruetter, ) or slightly faster (0.7 µmol/g/h, van Heeswijk, Morgenthaler, Xin, & Gruetter, ) glycogen turnover rates. The discrepancy on the measured turnover rates in our study and these previous publications could be caused by either the deepness of anesthesia that modulates brain activity and metabolism (Sonnay, Gruetter, & Duarte, ), or the brain levels of insulin that might stimulate glycogen synthesis (Fernandez et al, ; Muhič et al, ). Accordingly, administration of insulin to anaesthetized rats was previously reported to increase brain glycogen levels (Morgenthaler et al, ).…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Previous 13 C‐MRS studies in rats under light α‐chloralose anesthesia, have estimated similar (Choi, Tkác, Ugurbil, & Gruetter, ) or slightly faster (0.7 µmol/g/h, van Heeswijk, Morgenthaler, Xin, & Gruetter, ) glycogen turnover rates. The discrepancy on the measured turnover rates in our study and these previous publications could be caused by either the deepness of anesthesia that modulates brain activity and metabolism (Sonnay, Gruetter, & Duarte, ), or the brain levels of insulin that might stimulate glycogen synthesis (Fernandez et al, ; Muhič et al, ). Accordingly, administration of insulin to anaesthetized rats was previously reported to increase brain glycogen levels (Morgenthaler et al, ).…”
Section: Discussioncontrasting
confidence: 95%
“…levels of insulin that might stimulate glycogen synthesis (Fernandez et al, 2017;Muhič et al, 2015). Accordingly, administration of insulin to anaesthetized rats was previously reported to increase brain glycogen levels (Morgenthaler et al, 2006).…”
Section: Brain Glycogen Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important aspect confirmed by our findings is that IR and IGF‐IR display ligand‐independent activities that may, or may not, be related to the actions of their ligands (Boucher et al, ). In this regard, different authors have shown that IGF‐I and insulin also affect glucose handling by astrocytes at different levels, including enhanced glucose uptake (Kum et al, ; Masters et al, ) and/or enhanced glycogen production (Dringen and Hamprecht, ; Hamai et al, ; Muhic et al, ). These observations suggest that insulin peptides and their receptors form an intricate glucose regulatory network in astrocytes that may even act in apparently opposing manners.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors can regulate glycogen production and utilization in astrocytes, with insulin, insulin-like growth factor (IGF)-1 (305, 306), and leptin (203, 307) increasing their production of glycogen. More recently, ghrelin has been reported to possibly promote glycogenolysis in hypothalamic neurons (122).…”
Section: Functions Of Non-neuronal Cellsmentioning
confidence: 99%